Kegiatan â€œSakola Kahirupan-Gramatikalâ€ Berbasis Sekolah Alam Desa Curug Kecamatan Jasinga Dalam Mengedukasi Anak Cinta Alam Dan Lingkungan - Basith, Yudril (PRAXIS: Jurnal Pengabdian kepada Masyarakat, 2022)
The Kahirupan school activity, which is part of the community service program with the theme â€œImproving Awareness of Clean Livingâ€, was carried out in Curug Village, Jasinga District, Bogor Regency. There is a major problem that become a problem for our partners are the lack of optimal character instilling in the community regarding how to create and improve a healthy environment. With this program, it is hoped that it can provide benefits to children in particular and to society in general in order to prepare young people who have the character of a leader, critical thinking skills, ability to work in teams and morality and love the environment and nature. This program activity is carried out for a period of two (2) months. The planned activities are: nature school based activitie